The effect of Phyllanthus niruri on urinary inhibitors of calcium oxalate crystallization and other factors associated with renal stone formation - Freitas, A. M. [UNIFESP] (2002)
Objective To evaluate the effect of an aqueous extract of Phyllanthus niruri (Pn), a plant used in folk medicine to treat lithiasis. on the urinary excretion of endogenous inhibitors of lithogenesis, citrate, magnesium and glycosaminoglycans (GAGs).Materials and methods the effect of chronic (42 days) administration of Pn (1.25 mg/mL/day, orally) was evaluated in a rat model of urolithiasis induced by the introduction of a calcium oxalate (CaOx) seed into the bladder of adult male Wistar rats. the animals were divided into four groups: a sham control (16 rats): a control+Pri (six): CaOx+water instead of Pn (14): and CaOx+Pn (22). Plasma and urine were collected after 42 days of treatment for biochemical analysis and the determination of urinary excretion of citrate, magnesium and GAGs. the animals were then killed and the calculi analysed.Results the creatinine clearance or urinary and plasma concentrations of Na+, K+, Ca2+, oxalate, phosphate and uric acid were unaffected by Pn or the induction of lithiasis. Treatment with Pn strongly inhibited the growth of the matrix calculus and reduced the number of stone satellites compared with the group receiving water. the calculi were eliminated or dissolved in some treated animals (three of 22). the urinary excretion of citrate and magnesium was unaffected by Pn treatment. However, the mean (si)) urinary concentration of GAGs was significantly lower in rats treated with CaOx + Pn, at 5.64 (0.8 6) mg/g crcatinine. than when treated with CaOx+water, at 11.78(2.21)mg/g creatinine. in contrast, the content of GAGs in the calculi was higher in the CaOx + Pn rats. at 48.0 (10.4) g/g calculus. than in the CaOx+water group, at 16.6 (9.6) g/g calculus.Conclusion These results show that Pn has an inhibitory effect on crystal growth. which is independent of changes in the urinary excretion of citrate and Mg. but might be related to the higher incorporation of GAGs into the calculi.